2021
DOI: 10.1002/cti2.1263
|View full text |Cite
|
Sign up to set email alerts
|

Localised release of matrix metallopeptidase 8 in fatal cerebral malaria

Abstract: Objective. Cerebral malaria (CM) is a complication of Plasmodium falciparum malaria, in which progressive brain swelling is associated with sequestration of parasites and impaired barrier function of the cerebral microvascular endothelium. To test the hypothesis that localised release of matrix metallopeptidase 8 (MMP8) within the retina is implicated in microvascular leak in CM, we examined its expression and association with extravascular fibrinogen leak in a case-control study of post-mortem retinal samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…P. yoelii 17XL was placed closest to human CH in the PCA plot ( Figure 3g ), and the genes contributing most to PC1 and PC2 were again enriched in neutrophil degranulation and myeloid leukocyte activation GO terms ( Supplementary file 11 ). The finding that neutrophil degranulation and myeloid leukocyte activation pathway genes account for the greatest variation between human SM phenotypes and the mouse models is consistent with increasing evidence that different aspects of neutrophil function could contribute to pathogenesis or protection from SM in both humans and some mouse models ( Lee et al, 2018b ; Knackstedt et al, 2019 ; Georgiadou et al, 2021 ; Aitken et al, 2018 ; Feintuch et al, 2016 ; Sercundes et al, 2016 ). Taken together, the comparisons between mouse models and these three SM phenotypes in Gambian children suggest that P. yoelii 17XL recapitulates the profile of the most prominent changes in gene expression associated with human SM phenotypes more closely than the other mouse models.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…P. yoelii 17XL was placed closest to human CH in the PCA plot ( Figure 3g ), and the genes contributing most to PC1 and PC2 were again enriched in neutrophil degranulation and myeloid leukocyte activation GO terms ( Supplementary file 11 ). The finding that neutrophil degranulation and myeloid leukocyte activation pathway genes account for the greatest variation between human SM phenotypes and the mouse models is consistent with increasing evidence that different aspects of neutrophil function could contribute to pathogenesis or protection from SM in both humans and some mouse models ( Lee et al, 2018b ; Knackstedt et al, 2019 ; Georgiadou et al, 2021 ; Aitken et al, 2018 ; Feintuch et al, 2016 ; Sercundes et al, 2016 ). Taken together, the comparisons between mouse models and these three SM phenotypes in Gambian children suggest that P. yoelii 17XL recapitulates the profile of the most prominent changes in gene expression associated with human SM phenotypes more closely than the other mouse models.…”
Section: Resultssupporting
confidence: 80%
“…P. yoelii 17XL was originally described as a virulent clone causing CM-like pathology ( Yoeli and Hargreaves, 1974 ), but it has subsequently been replaced by P. berghei ANKA as the most commonly used model of experimental CM. Since one of the key pathological mechanisms leading to death in pediatric CM is brain swelling due to extravascular fluid leak ( Moxon et al, 2020 ), we examined the presence of extravascular fibrinogen ( Georgiadou et al, 2021 ) as an indicator of vascular leak in the brains of both P. berghei ANKA and P. yoelii 17XL infected mice compared to uninfected mice ( Figure 5c ). We found that brains from both infections had areas that stained positively for perivascular fibrinogen (indicative of vascular leak), while additionally some of the vessels from P. yoelii 17XL infected mice showed strong intravascular staining, suggestive of microthrombus formation ( Figure 5c, iv ), another mechanism that has been implicated in human CM ( Moxon et al, 2020 ; Georgiadou et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…SMIM1 has not been previously reported in malaria studies, but the correlation between its expression and parasitemia could indicate that it plays a role in regulating parasite development, possibly by modulating the amount of available hemoglobin (an important nutrient source for the parasites). Expression of MMP8, a neutrophil granule protein ( 23 ), has been shown to be elevated in the serum of individuals with uncomplicated malaria ( 32 ) and has been associated with malaria severity, particularly with cerebral malaria ( 8, 33 ). Although none of the individuals included in our study experienced cerebral malaria, it is possible that individuals with high parasitemia infections (and higher expression of MMP8) experienced more severe symptoms (symptom severity was not measured precisely in this cohort).…”
Section: Resultsmentioning
confidence: 99%
“…Feintuch et al reported higher levels of activated neutrophils in malarial retinopathy-positive CM pediatric patients [ 20 ]. Some studies hypothesized that neutrophils stimulated by the large numbers of sequestered parasites in the retinal and cerebral microvasculature in CM could degranulate, releasing MMP8 and leading to vascular endothelial barrier damage and vascular leakage [ 21 ]. Moreover, these vascular dysfunctions are common features of CM [ 22 ].…”
Section: Discussionmentioning
confidence: 99%